(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
The results of the study show that the Leaf index has changed significantly depending on the planting scheme and the genetic characteristics of the variety. The 76x9, 9x1, and 60x12, 5x1 planting schemes were found to be effective in further developing the leaf surface and optimizing the photosynthetic process. Guzor and Marvarid varieties have the highest LAI in the flowering and harvest phases, and have shown high potential in increasing yields. Planting schemes 76x9, 9x1 and 60x12, 5x1 created favorable conditions for the maximum formation of leaves. During the fruiting period, the high content of LAI had a positive effect on the photosynthetic ability and yield of the plant.